Rigid-flexible Coupling Dynamics Analysis of Hydraulic Excavator - Xie Qin; Wu Yunxin (Jixie chuandong)
In order to solve the problem of hydraulic excavator mechanical arm stress dynamic calculation,combining the virtual prototyping technology,finite element analysis techniques and dynamics theory,the modal reduction technique is used to establish flexible model of excavator boom and bucket rod. Furthermore,the rigid- flexible coupling system model of excavator is established and dynamics simulation is carried out. Finally,the stress of mechanical arm and hydraulic cylinder load are analyzed. The results show that the effect of structure static analysis is limited,the dynamics analysis which took motion and load characteristic into comprehensive consideration is more accurate in stress calculation. The maximum stress of boom and bucket rod is 107. 7 MPa and 40 MPa respectively. A theory basis for the structure optimization,accurate vibration control and life assessment for such structures is provided.